Salem Falls - Jodi Picoult
Jack buries his past, content to become the mysterious stranger who has appeared out of the blue. Addie, desperate for answers, must look into her heart -- and into Jack's lies and shadowy secrets -- for evidence that will condemn or redeem the man she has come to love.